Sistem Politik Islam di Zaman Nabi Muhammad S.A.W. - Amir, Ahmad Nabil (Jurnal Usuluddin, 2009)
This work provides an extensive and detailed study of the political system established in the time of the Prophet Muhammad p.b.u.h.. It studies the effective and skillful administration of Madinah in the 6th Century and highlights the challenging history of the Prophet p.b.u.h. and his Companions to generate a powerful system and radically reform the social custom and government of Madinah. This work also explores the greatness of Madinah focusing on the excellence dimension of human development and the triumph of culture, tradition and knowledge.